Dificuldades de aprendizagem na interpretação de textos escritos dos alunos da turma do 6° ano da escola professor Bernardino Pereira de Barros - PINHEIRO, Bernadete do Socorro da Silva (2023)
This study was conducted in the municipality of Abaetetuba Pará State, in order to identify the difficulties encountered in the process of teaching-learning regarding the interpretation of written texts of the students in the 6th grade Elementary School Teacher Bernardino Pereira de Barros. Initially we carried out a literature search on the Importance of the interpretation of texts written in Elementary Education. In a second step we carried out a field research, using as instruments two questionnaires applied to the Class Teacher and students of the 6th year of that school. The questionnaire administered to Professor is divided into three stages, which address issues related to teaching learning in order to point out the difficulties that teachers and students face in their daily claim school, as well as the need for reflection on the part of the same on the use of innovative methodologies, as effective strategy so that they can develop a rationale for understanding the texts. The other questionnaire used in this research was directed to students, in order to inquire them about the acceptance of this methodology and the contributions from the process of teaching / learning caused by the use of the same. As part of the process of data collection were developed with students activities interpretation of texts related to the content already covered this school year. The activities were carried out in the classroom. The analysis of the survey results are reported in the Results and Discussions of this work.